Plasmodium Resistance to Artemisinin Derivates due to Kelch-3 Gene Mutation - Trasi, Reqgi First (Talenta Publisher, 2021)
Artemisinin class of antimalarial drugs play an important role in controlling falciparum malaria after the emergence of resistance of Plasmodium falciparum to other antimalarial drugs such as chloroquine, sulfadoxine-pyrimethamine and mefloquine. Therefore, the presence of Plasmodium falciparum resistance to this class of drugs is threat to global efforts to eliminate this disease. Resistance of Plasmodium falciparum to artemisinin recently known to be associated with mutations in the propeller domain of the kelch-13 (K13) Plasmodium falciparum gene. The incidence of Plasmodium falciparum resistance due to mutations in the K13 gene, among others, can be found in Cambodia, Laos, Vietnam, China, Myanmar, Thailand and Africa. The presence of mutations in this gene will change the response of Plasmodium falciparum against oxidative stress induced by artemisinin by involving the proteasome-ubiquitin pathway. In addition, mutation K13 will also change the levels of PI3K and PI3P in the body of Plasmodium falciparum. PI3K and PI3P are lipids that essential for the development of Plasmodium falciparum from ring stage to schizont. Resistance to artemisinin will also provide phenotypic changes in the life cycle of Plasmodium falciparum in the form of elongation at the stage ring and transient shortening in trophozoite development. This resistance incident can be overcome, among others by prolonging the duration of treatment (from a 3-day regimen to a 4-day regimen) and combining artemisinin with proteasome inhibitors.